Antecedentes da intenção de compra de participantes de comunidades mobile - Oliveira, Marcelo Curth de (Universidade do Vale do Rio dos Sinos, 2018)
The present study aimed to propose and test a theoretical model that considered the relationships between cognitive involvement, affective involvement, social identity, social interaction ties, flow, and purchase intent. In order to achieve the objectives of the study, initially, it was carried out a systematic search for theoretical elements for creating the model and the proposition of hypotheses. The two studies were carried out with a survey, with 244 and 269 respondents, respectively, with participants from mobile communities (m-communities). The theoretical model was tested by using the Structural Equation Modeling (SEM). In addition to the test of the model and the hypotheses, it was also analyzed the mediation of the constructs: social identity constructs, social interaction ties, and flow among the constructs cognitive involvement, affective involvement, and purchase intention. The results showed that the affective involvement has a positive relationship on the social identity. This did not occur with the cognitive involvement in both studies. The relationship between social identity and purchase intention was supported only in the first study. For the other relationships, the first study supported the relationships between affective involvement and social identity with interactions ties, affective involvement, and social identity with flow. In the second study, results show support to the relationship between cognitive involvement and social identity with interaction ties, cognitive involvement and social identity with flow, in addition to the interaction ties with purchase intent. It is seen a mediator effect of the interaction ties with the involvements and purchase intent, with the first study being complete and the second study being partial. In addition, it was found that social identity and flow did not present a mediator effect between involvements and purchase intent. Finally, the thesis is a contribution in academic and managerial terms, making it possible for advances in understanding the background to the social identity and relationships with the purchase intent, while showing mediator effects of the interaction ties.
Keywords: Identidade social; Intenção de compra; Comunidades mobile; Social Identity; Purchase intent; Mobile communities; ACCNPQ::Ciências Sociais Aplicadas::Administração